Álvaro de las Casas, the Playwright. An Estimation - Vieites, Manuel F. (Madrygal. Revista de Estudios Gallegos, 2023)
Between 1926 and 1936, Álvaro de las Casas publishes a total of sixteen plays in Galician, quite different in their making and topics, and some relevant novels, while developing an intense cultural and political activity, now linked to the most traditional Catholicism and then within a movement for Galician national independence he contributes to articulate. With this article, based on a literature review and the appraisal of his plays, we point out their most unique features and consider the author’s contribution to our literature, showing how his comings and goings across the political and ideological spectrum are reflected in their form and content. As a conclusion, we highlight the richness and diversity of his dramas and their most substantive values.